Glycoprotein levels and oxidative lung injury in experimental diabetes: effect of oxovanadium(IV) complex based on thiosemicarbazone. (13th October 2021) - Bayrak, Bertan Boran; Tunali, Sevim; Bal-Demirci, Tulay; Ulkuseven, Bahri; Yanardag, Refiye
Abstract: Diabetes mellitus (DM) is chronic and metabolic disorder, which is mainly attributed by hyperglycemia. Vanadium salts and their oxo-complexes have been shown to possess insulin-mimetic and anti-diabetic activities in animal models and diabetic patients. The main goal of this study was to investigate the protective effect of oxovanadium(IV) complex based on thiosemicarbazone (VOL) [L: (N(1)-2, 4-dihydroxybenzylidene-N-(4)-2-hydroxybenzylidene-S-methyl-isothiosemicarbazidato-oxovanadium(IV)] on glycoprotein components levels and oxidative lung injury of streptozotocin (STZ)-induced diabetic rats. Male Swiss albino rats were separated into four groups. Group I ( n  = 5): Control (normal) animals, Group II ( n  = 5): Control animals administered with VOL, Group III ( n  = 6): STZ-induced diabetic animals, and Group IV ( n  = 5): STZ-induced diabetic rats treated with VOL. VOL was given to the experimental animals by gavage at a dose of 0.2 mM/kg body weight every day for 12 days. Diabetes was induced by single intraperitoneal injection of STZ (65 mg/kg body weight). On the 12th day, lung tissue samples were taken. Glycoprotein components, advanced oxidation protein products, protein carbonyl, hydroxyproline levels, and prolidase, arginase, xanthine oxidase, catalase, superoxide dismutase, glutathione peroxidase, glutathione reductase, glutathione-S-transferase and adenosine deaminase activities significantly increased whereas aryl esterase, paraoxonase-1, carbonic anhydrase, Na + /K + -ATPase activities remarkably decreased in lung tissue of diabetic rats. Treatment with VOL reversed these effects showing a beneficial effect. The present study shows that VOL has a protective effect against diabetes-induced lung damage as well as on abnormal glycoprotein component levels.